Teaching Vocabulary through Word Wall: A Qualitative Study Conducted at the Fifth Grade Students of a Public Elementary School in Bogor - Puspita, Esti; Muhajir, R. (ENGLISH JOURNAL, 2016)
The research concerned with teaching vocabulary through word wall at the fifth grade of a public elementary school in Bogor. The aims of this research are to find out the procedure of teaching vocabulary through word wall and to find out the student improvement in vocabulary mastery after being taught using word wall method and also to find out whether there are any difficulties faced by teacher in teaching vocabulary through word wall. In this research, the writers used qualitative method. The writers did observation, used questionnaire and gave interview to the teacher. The result showed that the procedure used by the teacher in teaching vocabulary was almost the same with the procedure of teaching learning activity, such as checks the attendance list and asks students to sit, pray and pay attention before they gives the material. In teaching learning process, the teacher teaches vocabulary through word wall. They reads the text, the asks the students to read it and finds out the difficulty words then they write it on the card, after all the teacher asks the students to come forward and stick the card on the wall. Students respond, enthusiastically to learn vocabulary through word wall. In evaluation, teachers always ask what they have learned for today and give them home work related to vocabulary. But, in using word wall media, firstly the teacher needed to prepare some materials such as; glue, paper, colour pens, etc. Based on the questionnaire, the students claimed that they agreed if teaching vocabulary through word wall could improve their vocabulary mastery and it could be proved by the total response’ percentage about 84,2%. And only 15.8% students did not agree that they could improve their vocabulary mastery through word wall method. Based on the interview, the writers concluded teaching vocabulary through word wall can make the students easier to learn the new words and to memorize it. Then there are no difficulties that faced by teacher, even sometimes they feels little bit lazy and difficult to prepare the material such as, paper, colourful pen, scissors and glue.